Fufang shenhua tablet, astragali radix and its active component astragaloside IV: Research progress on anti-inflammatory and immunomodulatory mechanisms in the kidney - Li, Run; Shi, Chunru; Wei, Cuiting; Wang, Chao; Du, Hongjian; Hong, Quan; Chen, Xiangmei (Frontiers in Pharmacology, 2023)
Background: Given the limited treatment options available for kidney disease, a significant number of patients turn to alternative therapies, including traditional Chinese medicine. Among these therapies, the Fufang Shenhua tablet (SHT) has garnered attention for its effectiveness in addressing the most common deficiency of Qi and Yin in chronic glomerulonephritis. Notably, the sovereign drug of SHT is Astragali Radix (AR), with the most abundant and effective component being Astragaloside IV (AS-IV) has been shown to possess anti-inflammatory and immunomodulatory properties, and it is extensively used in treating kidney diseases. Nevertheless, the molecular mechanisms underlying its action are numerous and intricate, and a comprehensive understanding is yet to be achieved. Aim of the review: Thus, we have thoroughly examined the existing research and outlined the advancements made in investigating the anti-inflammatory and immunomodulatory mechanisms of SHT, AR and its active component AS-IV, in relation to kidney health. This serves as a dependable foundation for conducting more comprehensive investigations, evaluating efficacy, and making further improvements in the future. Materials and methods: We conducted a comprehensive literature search utilizing multiple globally recognized databases, including Web of Science, Google Scholar, PubMed, ScienceDirect, ACS, Springer, and CNKI. The search keywords used in this study were "Fufang Shenhua tablet," "Astragali Radix," "Astragaloside IV," and "Anti-inflammatory" or "Immunity." Results: The mechanism of inflammation inhibition by SHT, AR and its active component AS-IV is mainly related to the signaling pathways such as NF-κB, TLRs, PI3K/AKT, and JAK-STAT. Immunomodulation exerts not only activating, stimulating, and regulating effects on macrophages and dendritic cells, but also on immune organs, T-lymphocytes, B-lymphocytes, and a myriad of cytokines. Moreover, the SHT, AR and AS-IV also demonstrate regulatory effects on renal cells. Conclusion: To summarize, SHT, AR and its active component AS-IV, exhibit notable therapeutic effects in kidney-related ailments, and their molecular mechanisms for anti-inflammatory and immunomodulatory effects have been extensively explored. Moreover, in-depth studies of unverified chemical components and regulatory mechanisms in SHT are required. It is our belief that with continued research, SHT, AR and its active component AS-IV are poised to pave the way for enhancing therapeutic outcomes in kidney-related ailments.